COVID-19 Impact Monitoring : Uganda, Round 2 - World Bank (World Bank, Washington, DC, 2020)
In June 2020, the Uganda Bureau of Statistics, with the support from the World Bank, has launched the High-Frequency Phone Survey on COVID-19 (coronavirus) to track the impacts of the pandemic on a monthly basis for a period of 12 months. The survey aimed to recontact the entire sample of households that had been interviewed during the Uganda National Panel Survey 2019/20 round and that had phone numbers for at least one household member or a reference individual. This report presents the findings from the second round of the survey that was conducted between July 31 and August 21, 2020.